(untitled) (Research, Society and Development, 2020)
This article focuses on an investigation on the interdisciplinary panorama in the relationship between parents and children during school activities and studies in their homes, at this time of pandemic and confinement. An exploratory and descriptive study, the instrument used for collecting survey data was made through Google Forms, to raise the perceptions and characteristics of this interaction between parents and children, at this moment in the midst of the COVID-19 pandemic. 66 undergraduate students from different areas of knowledge participated. The results indicated that those responsible for the children stated that they are collaborative, develop their work and study activities in a joint environment, consider that they have pedagogical training to assist in the execution of their children’s school activities. They use PC, Notebook and Smartphone equipment to develop study and work activities, most with broadband internet.